2022
DOI: 10.1002/cac2.12349
|View full text |Cite
|
Sign up to set email alerts
|

PLEK2 promotes cancer stemness and tumorigenesis of head and neck squamous cell carcinoma via the c‐Myc‐mediated positive feedback loop

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is one of the most frequent malignancies worldwide and is characterized by unfavorable prognosis, high lymph node metastasis and early recurrence. However, the molecular events regulating HNSCC tumorigenesis remain poorly understood. Therefore, uncovering the underlying mechanisms is urgently needed to identify novel and promising therapeutic targets for HNSCC. In this study, we aimed to explore the role of pleckstrin‐2 (PLEK2) in regulating HNSCC tumori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…ChIP-qPCR: The ChIP assay was performed using the EZ ChIP Chromatin Immunoprecipitation Kit (Millipore, Billerica, MA, USA), following a previously described protocol. [45] Briefly, DNA-protein cross-links were generated by fixing the cell samples with 1% formaldehyde for 10 min at room temperature. After washing three times with PBS, the samples were lysed in RIPA buffer and then subjected to sonication to fragment the genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP-qPCR: The ChIP assay was performed using the EZ ChIP Chromatin Immunoprecipitation Kit (Millipore, Billerica, MA, USA), following a previously described protocol. [45] Briefly, DNA-protein cross-links were generated by fixing the cell samples with 1% formaldehyde for 10 min at room temperature. After washing three times with PBS, the samples were lysed in RIPA buffer and then subjected to sonication to fragment the genomic DNA.…”
Section: Methodsmentioning
confidence: 99%
“…46,47 In addition, PLEK2 has also been shown to promote cancer cell stemness. 43 In this study, we found that the expression of α5-nAChR and PLEK2 was significantly Furthermore, we found a skeleton protein molecule, CFL1, with a high correlation with PLEK2 via UALCAN online analysis and in vitro and in vivo experiments in LUAD. CFL belongs to the ADF/CFL family, which contains two subtypes, CFL1 and CFL2.…”
Section: Discussionmentioning
confidence: 57%
“…In recent years, the biological function of PLEK2 in tumors has been widely studied. It has been shown to play a role in promoting the occurrence and development of lung cancer, gallbladder cancer, gastric cancer and other tumors 42–44 . In lung cancer, PLEK2 can directly interact with SHIP2 and degrade SHIP2 through phosphorylation‐mediated ubiquitination, while SHIP2 can negatively regulate the PI3K/AKT pathway by dephosphorylating PIP3 to PIP2 to restrict cancer progression 29,45 .…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Moreover, PLEK2 interacts with c-Myc to prevent its proteasomemediated degradation in head and neck squamous cell carcinoma. 43 Here, we determined that PLEK2 interacted with PPM1B in breast cancer cells (Figure 8A These results suggest that the PLEK2-PPM1B axis exerts prometastatic functions through the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, PLEK2 interacts with SHIP2 in non‐small‐cell lung cancer cells to target this protein for degradation, which leads to activation of the PI3K/Akt signaling pathway 14,15 . Moreover, PLEK2 interacts with c‐Myc to prevent its proteasome‐mediated degradation in head and neck squamous cell carcinoma 43 . Here, we determined that PLEK2 interacted with PPM1B in breast cancer cells (Figure 8A,C,D).…”
Section: Discussionmentioning
confidence: 78%